Analysis of the CP structure of the Yukawa coupling between the Higgs boson and τ leptons in proton-proton collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Journal of high energy physics)
The first measurement of the CP structure of the Yukawa coupling between the Higgs boson and tau leptons is presented. The measurement is based on data collected in proton-proton collisions at root s = 13 TeV by the CMS detector at the LHC, corresponding to an integrated luminosity of 137 fb(-1). The analysis uses the angular correlation between the decay planes of tau leptons produced in Higgs boson decays. The effective mixing angle between CP-even and CP-odd tau Yukawa couplings is found to be -1 +/- 19 degrees, compared to an expected value of 0 +/- 21 degrees at the 68.3% confidence level. The data disfavour the pure CP-odd scenario at 3.0 standard deviations. The results are compatible with predictions for the standard model Higgs boson.